Konseling Individual untuk Mengatasi Perilaku Bullying pada Perbedaan Gender di MTs Negeri Sleman Maguwoharjo Yogyakarta (Jurusan Bimbingan dan Konseling Islam, 2019)
This research is motivated by the fact that there are a number of students who experience bullying treatment on the opposite sex in MTS Negeri Sleman Maguwoharjo Yogyakarta. Students who bullying the opposite sex, researchers using individual service approaches are very appropriate and more effective in dealing with the bullying behavior, because individual service counseling is face-to-face with more in-depth methods of resolution. Ole therefore researchers have focused research on individual counseling services to address bullying behavior on gender differences and types of beullying to the opposite sex. The approach in this study uses descriptive qualitative that is by describing and giving meaning to the results of the study. The subjects of this study were 2 BK teachers, Madrasah heads and 3 students. The sampling technique used was purposive sampling. The sampling technique used was purposive sampling with snowballs. Data collection techniques using observation, interviews, and documentation. The results of the application of individual counseling services show that there are changes in the mindset and behavior of students, as well as a change in understanding of the world around them. With individual counseling services provided by counseling teachers, the counselee values ??his friends more and becomes a better person. The stages of individual counseling are carried out through several stages, namely: the planning stage, the implementation phase, the evaluation stage, and the follow-up. Then the type of bullying on gender differences done by students in MTS Negeri sleman Maguwoharjo Yogyakarta is 1) male type of bullying done to women is physical bullying, verbal violence 2) while female bullying to male students is verbal bullying.